Influence of bioceramic intracanal medication on the bond strength of bioceramic root canal sealer - Patrícia Maria ESCOBAR; Alice Corrêa SILVA-SOUSA; Rafael Verardino de CAMARGO; Marco SIMÕES-CARVALHO; Yara Teresinha SILVA-SOUSA; Jardel Francisco MAZZI-CHAVES; Gustavo DE-DEUS; Manoel Damião SOUSA-NETO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract To investigate the influence of the remaining volume of a new intracanal medication based on bioceramic compounds on the bond strength (BS) and formation of an adhesive interface between calcium silicate-based and epoxy resin-based root canal sealers. For this purpose, the specimens were distributed according to the intracanal medication (n = 26): Bio-C Temp (BCT) and Ultracal XS (UXS). The roots were scanned in microCT, and after 7 days, the medication was removed. Then a new scan was performed to evaluate the volume of medication remaining. Subsequently, 40 specimens were redistributed into 2 subgroups (n = 10) and filled according to the sealer used: AH Plus (AHP) and Bio-C Sealer (BCS), to assess the bond strength by using the push-out test, and the adhesive interface by confocal laser fluorescence microscopy (CLSM) and scanning electron microscopy (SEM). The t test showed a smaller remainder of BCT (1.77 ± 0.86) compared with UXS (10.47 ± 5.78), irrespective of the root third evaluated. The BS showed that teeth with BCT + BCS had higher bond strength values (3.70 ± 1.22) when compared to the other groups: BCT + AHP (2.15 ± 1.07), UXS + BCS (3.18 ± 1.09) and UXS + AHP (2.11 ± 1.02) (p<0.001). The cervical third had higher BS when compared with the middle and apical thirds (p < 0.001), and higher number of adhesive failures. The adhesive interface in SEM and CLSM images showed better adaptation for the association between BCT + BCS. Intracanal medication and silicate-based endodontic sealer appeared to interact chemically by forming a biomineralizing layer, allowing for an increase in the bond strength and forming an adhesive interface between the materials, with no or less gap formation.